Lifecycle Cost Management for Offshore Marine Renewable Energy Wind Infrastructure: An Integrated Model Using Circular Economy Principles - Mohammad, Suleiman Ibrahim; Qrain, Badrea Al; Alenazi, Sultan Alaswad; Vasudevan, Asokan; Shelash, Anber Abraheem; Ali, Imad (Sustainable Marine Structures, 2025)
As offshore wind infrastructure becomes more important to global efforts to reduce carbon emissions, it is becoming more important to connect lifecycle cost management with circular economy (CE) principles. When looking at the long-term costs of infrastructure, traditional lifecycle cost models often fail to account for residual value recovery, material circularity, or environmental externalities. This study creates a unified analytical framework that adds CE strategies to lifecycle cost modelling for offshore wind systems, such as turbines, substructures, moorings, and floating platforms.  The method uses multi-objective optimization and system dynamics simulation along with net present value (NPV) modelling, material flow analysis, and carbon-adjusted cost accounting. We modelled project-level datasets over 25 years to look at the trade-offs between economic and environmental factors in both linear and circular lifecycle scenarios. We use Python, MATLAB, and OpenLCA to look at key metrics like the Material Circularity Indicator (MCI), estimates of residual value, and internalized carbon costs. The results show that circular infrastructure strategies greatly lower lifecycle costs while also increasing material recovery and carbon efficiency. Scenario simulations showed that CE-based configurations could cut costs by up to 18% and emissions over the life of the product by 22%. Regression and sensitivity analyses showed that MCI, CAPEX, and circular design strategies are good at predicting residual value and long-term economic performance. This study adds a new, evidence-based model for making decisions about infrastructure that takes into account financial, environmental, and material circularity. ER